Chiral phase-transfer catalysis in the asymmetric α-heterofunctionalization of prochiral nucleophiles - Schörgenhumer, Johannes; Tiffner, Maximilian; Waser, Mario (Beilstein Journal of Organic Chemistry, 2017)
Chiral phase-transfer catalysis is one of the major catalytic principles in asymmetric catalysis. A broad variety of different catalysts and their use for challenging applications have been reported over the last decades. Besides asymmetric C–C bond forming reactions the use of chiral phase-transfer catalysts for enantioselective α-heterofunctionalization reactions of prochiral nucleophiles became one of the most important field of application of this catalytic principle. Based on several highly spectacular recent reports, we thus wish to discuss some of the most important achievements in this field within the context of this review.
Keywords: amination; chlorination; fluorination; hydroxylation; thioetherification